A Theoretical Note on Sector-specific FDI Inflow in Developing Economies and the Real Exchange Rate. Issue 2 (May 2020) - Mandal, Biswajit; Bhattacharjee, Prasun
Using a hybrid of the Heckscher–Ohlin model and specific factor model of trade, this article considers the phenomenon of FDI inflows only in the exportable sector of developing economies. We investigate the impact of such capital flow on factor prices and the real exchange rate (RER) in the host country. Our results indicate that the exportable production expands while both the non-traded good production and the return to the factor specific to the non-traded good decrease, consequent upon an inflow of capital specific to the exportable sector. The effect of such inflow of foreign capital on the RER is unambiguous and it increases. JEL Codes: F1, F21, F31